Optimization of Biodiesel Production from Jatropha curcas Oil by Base Catalyzed Transesterification Process - Poojitha Reddy Giri; Keerthana Reddy; Hanusha Durisety; Madhuri Pydimalla (Technological Innovation in Engineering Research Vol. 1, 2022)
The major goal of this study was to examine the attributes of biodiesel produced using homogeneous and heterogeneous base catalysts. To evaluate its potential as a diesel substitute, the parameters were compared to ASTM specified fuel properties. The base-catalyzed transesterification process was employed to manufacture biodiesel from Jatropha curcas oil in this study. As homogeneous and heterogeneous base catalysts, KOH and CaO were utilised. The biodiesel was then subjected to a variety of characterisation procedures, including acid number, fire point, flash point, cloud point, and pour point, as well as fluid parameters such as density and specific gravity. The results obtained (Example: Fire point: 126, Specific gravity: 0.87) using KOH catalyst were promising as the values were in line with ASTM standard. The attained biodiesel characteristics (specific gravity and density) are close to that of petrol and diesel. As a result of this study’s findings, a systematic comparison of two different catalysts was conducted, and it was discovered that KOH is the best catalyst, as it is both affordable and scalable to achieve maximum yield.